The Use and Economic Value of the 3K SNP Genomic Test for Calves on Dairy Farms - Albert De Vries; David T. Galligan; John B. Cole (EDIS)
The availability of genomic tests is rapidly changing genetics in the dairy industry. AI companies have been using genomics to select AI sires. Now also commercial dairy producers can find value in testing their calves to help decide which ones to keep. This 5-page fact sheet was written by Albert De Vries, David T. Galligan, and John B. Cole, and published by the UF Department of Animal Science, September 2011.